The anti-inflammatory and antitumor effects of medicinal plants: Arctium lappa, Solanum torvum and Lobelia inflata - Paschoal , Bárbara S; Carvalho, Gabriela C.; Cauzzo, Gabriela; Campo, Vanessa L.; Zoccal, Karina F.; Tefé-Silva, Cristiane (Revista Saúde & Diversidade, 2020)
Introduction: Medicinal plants have been used since antiquity to treat illnesses and injuries. Considering their global use, many natural products have been investigated with the aim to get new drugs. Methods: The search was based on relevant articles indexed in PubMed, Scielo and Scopus. The search terms used were: medicinal plants, Arctium lappa, Solanum torvum, Lobelia inflata, anti-inflammatory effects, antimicrobial activity and antitumor effects. Development: Arctium lappa leads to the inhibition of nitric oxide synthase (iNOS) expression and nitric oxide (NO) production and inhibits the growth of some tumor cell lines. Solanum torvum can promote inhibition of inflammatory mediators release, and reduces the melanoma formation. Lobelia inflata can reduce the number of white blood cells, the TNF-α and IL-6 levels and the melanoma growth. Conclusion: The active principles present in these medicinal plants, including flavonoids and other phenolic compounds with antioxidant activity, can scavenge free radicals and therefore be effective against tumors, such as melanoma and skin cancer.